Bjerknes compensation mechanism as a possible trigger of the low-frequency variability of Arctic amplification - Latonin Mikhail; Bashmachnikov Igor L'vovich; Bobylev Leonid Petrovich (Russian Journal of Earth Sciences)
The causes of Arctic amplification are widely debated, and a cohesive picture has not been obtained yet. This study has investigated the role of the Atlantic meridional oceanic and atmospheric heat transport into the Arctic in the emergence of Arctic amplification. The integral advective fluxes in the layer of Atlantic waters and in the lower troposphere were considered. The results show a strong coupling between the meridional heat fluxes and regional Arctic amplification in the Eurasian Arctic on the decadal time scales (10–15 years). We argue that the low-frequency variability of Arctic amplification is regulated via the chain of oceanic heat transport — atmospheric heat transport — Arctic amplification. The atmospheric response to the ocean influence occurs with a delay of three years and is attributed to the Bjerknes compensation mechanism. In turn, the atmospheric heat and moisture transport directly affects the magnitude of Arctic amplification, with the latter lagging by one year. Thus, the variability of oceanic heat transport at the southern boundary of the Nordic Seas might be a predictor of the Arctic amplification magnitude over the Eurasian Basin of the Arctic Ocean with a lead time of four years. The results are consistent with the concept of the decadal Arctic climate variability expressed via the Arctic Ocean Oscillation index.